Comparison of the efficacy of the anterolateral thigh flap for perforator localization in the repair of head and neck soft tissue defects patients: A protocol study for a randomized controlled trial. Issue 50 (11th December 2020) - Sheng, Jiangfeng; Li, Chao; Tang, Ping; Hu, Jun; Ma, Liying; Qin, Gang
Abstract: Background: Head and neck tissue defects cause great physical and psychological damage to patients. Therefore, accurate positioning of perforating vessels before operation is of great significance for improving the success rate of flap preparation and avoiding unnecessary incision injury. Methods/Design: A total of 60 patients with laryngeal cancer in otolaryngology, Department of Otolaryngology Head and Neck Surgery, Affiliated Hospital of Southwest Medical University and the Third People's Hospital of Mianyang city from October 2020 to October 2021 will be selected and randomly divided into CT angiogram (CTA) group (n=20), mimics group (n = 20) and CTA + mimics group (n = 20) according to the numerical table. Patients in the CTA group will receive CTA examination of lower extremities. Patients in mimics group will receive digital technology in the positioning of perforator. Patients in CTA + mimics group will receive CTA + digital technology. All the patients will receive the flap cutting and the flap making; the doctor will determine the perforation branch of the flap with 3-D visual positioning, measure the preoperative indicators intraoperatively and complete the wound repair. Finally, the survival rate, sensitivity, specificity and accuracy of the flap will be measured. Discussion: The anterolateral thigh flap has been widely used to repair various tissue defects and has obtained good clinical results. The extensive clinical application mainly focuses on 2 aspects, namely the study of vascular anatomy of lateral flap and the exploration of preoperative flap design technology. Perforator is the direct blood supply source of anterolateral thigh flap, so it is particularly important to study the anatomy of perforator. Therefore, this study will reveal CTA combined with digital technology in the vascular anatomy of the anterior external femoral flap and the design of the flap before and during surgery, so as to provide help for the repair of tissue defects. Trial registration: It has been registered at http://www.chictr.org.cn/listbycreater.aspx (Identifier: ChiCTR2000038951), Registered on October 10th, 2020.